2017
DOI: 10.1111/hepr.12868
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of combined albumin–bilirubin and tumor–node–metastasis staging system in patients who underwent hepatic resection for hepatocellular carcinoma

Abstract: This retrospective analysis showed that, in post-hepatectomy patients with HCC, the ALBI-T score is predictive of worse recurrence-free survival, even when adjustments are made for other known predictors. However, modified JIS is better than ALBI-T in predicting overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…Moreover, albumin, total bilirubin, and prothrombin time are treated as semiquantitative factors in that classification. On the other hand, ALBI-T, which consists of ALBI grading and TNM staging, has been proposed as a new total staging system for HCC [12], and validation studies have already been reported [29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, albumin, total bilirubin, and prothrombin time are treated as semiquantitative factors in that classification. On the other hand, ALBI-T, which consists of ALBI grading and TNM staging, has been proposed as a new total staging system for HCC [12], and validation studies have already been reported [29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…Accuracy of the ALBI score might surpass that of the Child–Pugh score in predicting the occurrence of severe post‐hepatectomy complications. Combined with the tumor–node–metastasis classification, prognosis prediction for recurrence‐free survival using the ALBI score improved its accuracy in a large cohort of post‐hepatectomy patients …”
Section: Discussionmentioning
confidence: 99%
“…Integrating a liver function index into the TNM system can improve its prognostic value. Harimoto N et al established the ALBI-TNM staging system by integrating the albumin-bilirubin (ALBI) grade into the TNM and found that the ALBI-TNM score was predictive of worse recurrence-free survival 17 . Replacing the Child-Pugh grade with a new liver function index/grade is also a common way to build a new staging system and to improve its prognostic ability.…”
Section: Introductionmentioning
confidence: 99%